PELATIHAN PERANCANGAN PROTOTYPE APLIKASI PEMASARAN UNTUK MENDUKUNG KEIKUTSERTAAN GEN Z PADA FESTIVAL INOVASI DAN KEWIRAUSAHAAN SISWA INDONESIA (FIKSI) - Endra Rahmawati; Ayouvi Poerna Wardhanie; Sri Hariani Eko Wulandari; Pradita Maulidya Effendi (Jurnal Abdi Insani, 2023)
FIKSI 2022 activities aim to form community relations and networks for high school students who can support entrepreneurial activities. The number of fields offered at FIKSI creates anxiety for SMA/MA students to determine their interests and competencies. By looking at the conditions of existing business trends, many entrepreneurial activities begin with product marketing using information technology. Therefore, there is a need for Training and Assistance in Product Marketing Application Prototype Design Analysis as an Effort to Support Generation Z's Participation in the Indonesian Student Innovation and Entrepreneurship Festival (FIKSI) in this Digital Age. This training and mentoring activity is divided into 4 sessions, namely introduction of resource persons, delivery and presentation of material, practical use of tools, and a final evaluation session. The results of the final evaluation showed that 85.11% of high school students could understand and accept the material for this FIKSI Training and Assistance activity.